The SLOSS dilemma: A butterfly case study - Baz, A; GarciaBoyero, A (BIODIVERSITY AND CONSERVATION, 1996)
Butterfly species richness is examined on simulated archipelagoes of 2, 3, 4 and 5 holm oak forest fragments in the Guadalajara Province (central Spain). It is shown that there are more species on several small `islands' than on a single island. Also, species number increases with the number of fragments that form the archipelago, and with the average distance between islands within the archipelago. Thus, we conclude, at least for butterflies in a system of fragmented helm oak forests in central Iberia, that the best strategy in order to maximize the conservation of species richness is the creation of a net of some small and scattered reserves.
Keywords: average distance; butterflies; Central Spain; simulated archipelagoes; SLOSS